2013
DOI: 10.5762/kais.2013.14.11.5923
|View full text |Cite
|
Sign up to set email alerts
|

Model Tests for Measurement of Lateral Earth Pressure on Retaining Wall with the Relieving Platform Using Jumoonjin Sand

Abstract: Recently, the retaining wall with the relieving platform has received increasing interests also in Korea in that it can reduce the lateral earth pressure and provide more stability than conventional retaining wall. Previous studies with model tests studies covered only a limited test conditions. In this study, total 15 model tests were performed for various conditions with improved model test apparatus to confirm the effect of decreasing the lateral earth pressure on the retaining wall with the relieving platf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…The stress deflects only when approaching the unloading plate gradually due to the action of the plate on the soil, and the earth pressure distribution presents a certain difference. Below the unloading plate, the theoretical solution of earth pressure under the two displacement modes is closer to results of Moon et al (2013), and Chauhan and Dasaka (2021); however, the corresponding numerical solution of earth pressure is larger.…”
Section: Casesupporting
confidence: 68%
See 1 more Smart Citation
“…The stress deflects only when approaching the unloading plate gradually due to the action of the plate on the soil, and the earth pressure distribution presents a certain difference. Below the unloading plate, the theoretical solution of earth pressure under the two displacement modes is closer to results of Moon et al (2013), and Chauhan and Dasaka (2021); however, the corresponding numerical solution of earth pressure is larger.…”
Section: Casesupporting
confidence: 68%
“…Above the unloading plate, the numerical and theoretical solutions of the earth pressure under the two displacement modes do not significantly differ from the results of Moon et al (2013), Chauhan and Dasaka (2021). The stress deflects only when approaching the unloading plate gradually due to the action of the plate on the soil, and the earth pressure distribution presents a certain difference.…”
Section: Casementioning
confidence: 67%
“…And model test results were compared with the analyzed results by the 2D finite element method and values driven from the theoretical equation. Model tests between the retaining wall with a relieving platform and the cantilever retaining wall were performed and showed that the reduction of the lateral earth pressure and deformation of the wall was indicated clearly on the retaining wall with a relieving platform [13,14]. And the overall stability was increased by the relieving platform.…”
Section: Introductionmentioning
confidence: 99%
“…e retaining wall is not a new type of construction in countries such as China, Korea, India, and Russia. Model tests have been performed to determine the distribution of the Earth pressure and confirm the effect of decreasing the lateral Earth pressure on the retaining wall with relieving platform [18][19][20]. From the model tests, comparisons between the retaining wall with relieving platform and the cantilever retaining wall show that the reduction of the lateral Earth pressure and deformation of wall are indicated clearly on the retaining wall with a relieving platform, and the overall stability is increased by the relieving platform [21].…”
Section: Introductionmentioning
confidence: 99%